2000
DOI: 10.1088/0031-9155/45/6/315
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular motion reconstruction from planar tagged MR images: a comparison

Abstract: Through recent development of MR techniques, it is now possible to assess regional myocardial wall function in a non-invasive way. Using MR tagging, space is marked with planes which deform with the tissue, providing markers for tracking the local motion of the myocardium. Numerous methods to reconstruct the three-dimensional displacement field have been developed. The aim of this article is to provide a framework to quantitatively compare the performance of four methods the authors have developed. Five sets o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 37 publications
4
64
0
Order By: Relevance
“…Part of the error comes from the fact that different tracking algorithms will compute different tag line centers, and part of the error comes from the data smoothing effect of the deformation model. In Declerck et al (23), the second type of tag line errors were reported for four existing cardiac deformation reconstruction algorithms (6,8,14,23), and these errors ranged from 0.5 to 1.0 pixel. The RMS tag line errors in this article are also in this range, and include the inherent errors of tracking tag lines in noisy data, which are not included in the errors reported by Declerck et al (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Part of the error comes from the fact that different tracking algorithms will compute different tag line centers, and part of the error comes from the data smoothing effect of the deformation model. In Declerck et al (23), the second type of tag line errors were reported for four existing cardiac deformation reconstruction algorithms (6,8,14,23), and these errors ranged from 0.5 to 1.0 pixel. The RMS tag line errors in this article are also in this range, and include the inherent errors of tracking tag lines in noisy data, which are not included in the errors reported by Declerck et al (23).…”
Section: Discussionmentioning
confidence: 99%
“…In Declerck et al (23), the second type of tag line errors were reported for four existing cardiac deformation reconstruction algorithms (6,8,14,23), and these errors ranged from 0.5 to 1.0 pixel. The RMS tag line errors in this article are also in this range, and include the inherent errors of tracking tag lines in noisy data, which are not included in the errors reported by Declerck et al (23). From this perspective, the RMS tag line differences reported for COTTER are comparable to and possibly better than those reported by existing techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of approaches can be employed to perform this estimation. The tag data can be interpolated to solve iteratively for a set of discrete displacements [49], the data can be used to solve for low-order basis functions in finite element models of the heart [70], or the displacement field of the entire left ventricle can be fit using all of the available data [23], [53], [54]. Recently parameter-free models of left ventricular strain have been developed [25], as well as field models based on B-splines [3], [56].…”
Section: Estimation Of Local Myocardial Strainsmentioning
confidence: 99%
“…Recently parameter-free models of left ventricular strain have been developed [25], as well as field models based on B-splines [3], [56]. Each of these methods has different tradeoffs between the stability of the solution, and the spatial resolution of the strain field [23]. Fig.…”
Section: Estimation Of Local Myocardial Strainsmentioning
confidence: 99%